2006
DOI: 10.1152/ajpheart.00133.2005
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-dependent plasticity of fenestrated capillaries in the normal adult microvasculature

Abstract: Unlike during development, blood vessels in the adult are generally thought not to require VEGF for normal function. However, VEGF is a survival factor for many tumor vessels, and there are clues that some normal blood vessels may also depend on VEGF. In this study, we sought to identify which, if any, vascular beds in adult mice depend on VEGF for survival. Mice were treated with a small-molecule VEGF receptor (VEGFR) tyrosine kinase inhibitor or soluble VEGFRs for 1-3 wk. Blood vessels were assessed using im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
609
4
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 701 publications
(652 citation statements)
references
References 70 publications
33
609
4
6
Order By: Relevance
“…axitinib induced hypothyroidism in preclinical studies, 57,58 but this result has not yet been reported in clinical trials. the inci dence of primary hypothyroidism as an adverse effect of tKis is variable.…”
Section: Conclusion and Future Areas Of Researchmentioning
confidence: 95%
See 2 more Smart Citations
“…axitinib induced hypothyroidism in preclinical studies, 57,58 but this result has not yet been reported in clinical trials. the inci dence of primary hypothyroidism as an adverse effect of tKis is variable.…”
Section: Conclusion and Future Areas Of Researchmentioning
confidence: 95%
“…The majority of hypothyroid patients with TKi-related hypothyroidism, pretreated with cytokines 26 or imatinib 29 ; in first-line trial of sunitinib vs interferon-α, 49 sorafenib vs placebo 50 and combination of sorafenib with interferon-α, 51 57,58 No specific data Dose dependent thyroid capillary regression; TsH was 19-fold higher than in the control group. Most of the capillaries re-grew within 2 weeks after treatment withdrawn (reversible process) 58 Imatinib increase of the nondeiodination clearance (induction of hepatic microsomal enzymes) 25 increased requirement of levothyroxine No specific data Abbreviations: reT, rearranged during transfection; TK, tyrosine kinase; TKi, tyrosine kinase inhibitor; TsH, thyroid stimulating hormone; veGFr, vascular endothelial growth factor receptor.…”
Section: Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential role of VEGF during embryonic development is well established and widely accepted, but this dependency was thought not to persist into adult life. Yet, actions of VEGF are beginning to be identified in normal organs of the adult, examples being the role of VEGF in function and survival of normal blood vessels, blood pressure regulation, and renal, neurological, and hepatic function (Horowitz et al, 1997;Eremina et al, 2003;DeLeve et al, 2004;Kamba et al, 2006;Lambrechts and Carmeliet, 2006). Findings from studies of structural or functional changes in normal organs after inhibition of VEGF signalling provide clues into mechanisms of side effects in cancer patients treated with VEGF inhibitors.…”
Section: Preclinical Evidence Of Effects Of Vegf Inhibition On the Nomentioning
confidence: 99%
“…A number of studies have shown that expression of a variety of angiogenic factors, including VEGF, VEGF-B, placental growth factor, and FGF-2 are regulated by androgens in whole prostate or cultured prostate epithelial cells (14)(15)(16)(17)(18)(19)(20)(21). As recent studies have indicated that expression of VEGF is necessary not only for initial vascularization but also for maintenance of some normal adult capillary beds (22), decreased production of VEGF or other angiogenic factors by the prostatic epithelium or stroma may be responsible for the vascular regression observed after castration. Thus, the vascular endothelial cells may be responding to local paracrine signaling by the androgen-responsive prostate epithelial or stromal cells.…”
Section: Discussionmentioning
confidence: 99%